HYGIENIC ASPECTS OF OCCUPATIONAL INCIDENCE IN THE KEMEROVO REGION - Сувидова, Татьяна Анатольевна; Олещенко, Анатолий Михайлович (Medicine in Kuzbass, 2018)
Research subject – occupational incidence (OI). Objective – complex hygienic assessment of occupational incidence in the Kemerovo Region (KR) along with obtaining computer models of its dynamics, cause-and-effect dependencies, clustering by the types of economic activities, territories, professions. Methods. For the study, we used a computer database of social-hygienic monitoring (SHM) on 8125 cases of occupational diseases diagnosed in 2005-2015 in KR. On the basis of the software package Statistica 6.0 with the application of autocorrelation, correlation and regression, factor, cluster analyses, computer modeling the components of the sanitary and epidemiological situation related to OI was conducted. Main results. In 2005-2015 various-directional trends of the changes in OI levels during the major economic activities and the contribution shares of the factors of working conditions in OI were observed. The values of the decrease in work experience in the profession in case of occurrence of the most widespread occupational diseases depending on the degree of the 3rd class of working conditions were established. The contribution shares of the factors in the occurrence of occupational diseases were determined. The clusters of the similarity of economic activities, miner’s cities, mass professions on the set of OI indicators were obtained. Application field. Bodies and institutions of Rospotrebnadzor. Conclusions. Hygienic OI assessment on the basis of computer modeling has revealed new aspects of its formation in KR important for the implementation of risk-oriented direction of realizing the state sanitary-and-epidemiologic supervision.